One spoon on this earth - Hyŏn, Ki-yŏng, 1941-; Lee, Jennifer M. (Jennifer Myunghee) (Champaign, [Illinois] Dalkey Archive Press, 2013)
"An autobiographical novel that takes a life to pieces, putting forward not a coherent, straightforward narrative, but a series of dazzling images ranging from the ordinary to the unbelievable, fished from the depths of the author's memory as well as from the stream of his day-to-day life as an adult author. Interweaving flashes of the horrific Jeju Uprising and the Korean War with pleasant family anecdotes, stories of schoolroom cruelty, and bizarre digressions into his personal mythology, One Spoon on this Earth stands a sort of digest of contemporary Korean history as it might be seen through the lens of one man's life and opinions"--
"Originally published in Korean as Chisang e sutkarak hana by Silchʻŏn Munhaksa, Seoul, 1999"--Verso title page.
"Published in collaboration with Korea Literature Translation Institute"
Keywords: Autobiographical memory -- Fiction; Cheju Island (Korea) -- Fiction; Korea -- Fiction; Psychological fiction; Autobiographical fiction